2017
DOI: 10.1007/s11274-017-2327-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of orientation and flexibility of peptide linkers on T. maritima lipase Tm1350 displayed on Bacillus subtilis spores surface using CotB as fusion partner

Abstract: Fusion protein construction often requires peptide linkers for prolonged conformation, extended stability and enzyme activity. In this study a series of fusion between Thermotoga maritima lipase Tm1350 and Bacillus subtillis coat protein CotB, comprising of several peptide linkers, with different length, flexibility and orientations were constructed. Effects of temperature, pH and chemicals were examined, on the activity of displayed enzyme. The fusion protein with longer flexible linkers L9 [(GGGGS)] and L7 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Hinc et al [ 85 ] compared the expression efficiency of fusion proteins in cotZ -UreA versus cotB -GGGEAAAKGGGG-UreA, finding that the latter, which incorporates flexible linker peptides, expressed up to 100-fold more recombinant proteins on a spore than the former. Although various types of linker peptides have been designed over time [ 86 , 87 ], the ideal configuration remains elusive. The selection of different anchor proteins [ 8 , 85 ] and ligation strategies [ 88 , 89 ] can also significantly enhance the presentation efficiency of exogenous proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Hinc et al [ 85 ] compared the expression efficiency of fusion proteins in cotZ -UreA versus cotB -GGGEAAAKGGGG-UreA, finding that the latter, which incorporates flexible linker peptides, expressed up to 100-fold more recombinant proteins on a spore than the former. Although various types of linker peptides have been designed over time [ 86 , 87 ], the ideal configuration remains elusive. The selection of different anchor proteins [ 8 , 85 ] and ligation strategies [ 88 , 89 ] can also significantly enhance the presentation efficiency of exogenous proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A glycine-rich linker is more flexible than a linker of the same length composed of non-glycine residues. Jawad et al reported that after inserting a (GGGGS) 4 linker between CotB and Tm1350 from Thermotoga maritime MSB8, the catalytic efficiency of the fusion protein was 1.29 times higher than the activity of the original under optimum temperature and pH (Ullah et al 2017 ). Ruan et al showed that the permeation activity of TD1–hEGF, a fusion protein composed of TD1 and human epidermal growth factor (hEGF) connected with the flexible linker (GGGGS), can be inhibited by the energy inhibitor, rotenone or oligomycin (Ruan et al 2014 ).…”
Section: Design and Selection Of Linker Between The Fusion Proteinmentioning
confidence: 99%
“…The addition of a suitable length of linker peptide between the anchor and target proteins seems to help to separate the active part of the protein from the cell wall, creating space for substrate access and improving the activity of the display enzyme ( Washida et al, 2001 ; Ullah et al, 2017 ; Yang et al, 2019 ).…”
Section: Cell Surface Display Systems In S Cerevisiaementioning
confidence: 99%